Hardwired Behavior What Neuroscience Reveals about Morality - Tancredi, Laurence R (Cambridge University Press, 2013)
In preparation for writing this book I have reviewed the relevant scientific literature from many specialties, most particularly the neurosciences, genetics, psychiatry, psychology, primatology, and the social sciences. I have focused predominantly on what is known at this time from neuroscience research. But I have also explored the implications of the course of neuroscience research in terms of likely findings for the future.